2013
DOI: 10.1158/1055-9965.epi-13-0651
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Soluble CD27 and CD30 in Workers Exposed to 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD)

Abstract: Previous studies suggest that 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) exposure may be associated with non-Hodgkin lymphoma (NHL) but findings remain inconclusive. There is a need for mechanistic studies to evaluate the biologic plausibility of this association. In this cross-sectional study, we investigated changes in plasma levels of interleukin 1 receptor antagonist (IL1RA) and soluble (s)CD27 and sCD30 which have been found to be predictive of lymphoma, among workers of a cohort occupationally exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Elevated levels of soluble CD27, cleaved from CD27‐positive cells, have been observed in many infectious and autoimmune diseases and have been proposed as a marker of immune activation . Recently, two studies have shown that exposure to environmental exposures suspected to be lymphomagens ( i.e ., trichloroethylene and 2,3,7,8‐tetrachlorodibenzo‐ p ‐dioxin) pertubated plasma levels of sCD27 and sCD30 . This may indicate that lymphomagens exert their effect by dysregulation of the immune system as represented by changes in the B‐cell activation markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of soluble CD27, cleaved from CD27‐positive cells, have been observed in many infectious and autoimmune diseases and have been proposed as a marker of immune activation . Recently, two studies have shown that exposure to environmental exposures suspected to be lymphomagens ( i.e ., trichloroethylene and 2,3,7,8‐tetrachlorodibenzo‐ p ‐dioxin) pertubated plasma levels of sCD27 and sCD30 . This may indicate that lymphomagens exert their effect by dysregulation of the immune system as represented by changes in the B‐cell activation markers.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recently, two studies have shown that exposure to environmental exposures suspected to be lymphomagens (i.e., trichloroethylene and 2,3,7,8-tetrachlorodibenzo-p-dioxin) pertubated plasma levels of sCD27 and sCD30. 30,31 This may indicate that lymphomagens exert their effect by dysregulation of the immune system as represented by changes in the B-cell activation markers.…”
Section: Cancer Epidemiologymentioning
confidence: 99%
“…Saberi Hosnijeh et al. (, , ) investigated immune parameters in occupational cohorts of workers exposed from 1953 to 1969, or from 1955 to 1986, with accidental high exposure in 1963. The studies were based on a small numbers of subjects on the same or overlapping cohorts.…”
Section: Assessmentmentioning
confidence: 99%
“…To explore the potential mechanisms underlying dioxin­(-like) exposure toxicity, we used a network-based integration approach to evaluate the relationship between the metabolic pathways associated with dioxin­(-like) exposures and immune phenotypic end points. Immune markers, including cytokines and growth factors ( n = 21), hematologic parameters (i.e., cell counts) ( n = 23), humoral immunity markers [immunoglobulins (Ig) and complement factors (C)] ( n = 7), and lymphoma makers ( n = 3), were previously measured for factory A workers (Table S3).…”
Section: Methodsmentioning
confidence: 99%